Uncommon EGFR mutations in non-small-cell lung cancer: A systematic literature review of prevalence and clinical outcomes. (February 2022) - John, Thomas; Taylor, Aliki; Wang, Huifen; Eichinger, Christian; Freeman, Caroline; Ahn, Myung-Ju
Abstract: Mutations in exons 18–21 of the epidermal growth factor receptor gene ( EGFR ) can confer sensitivity to EGFR-tyrosine kinase inhibitors (EGFR-TKIs) in patients with non-small-cell lung cancer (NSCLC). Deletions in exon 19 or the exon 21 L858R substitution comprise approximately 85% of mutations, but comparatively few data are available on the remaining "uncommon" mutations. We conducted a systematic literature review to identify evidence on uncommon EGFR mutations in locally advanced/metastatic NSCLC (PROSPERO registration number: CRD42019126583). Electronic screening and congress searches identified studies published in 2012–2020 including patients with locally advanced/metastatic NSCLC and uncommon EGFR mutations (excluding T790M). We assessed the prevalence of uncommon mutations (in studies using direct sequencing of exons 18–21), and compared response to treatment and progression-free survival (PFS) in patients with common versus uncommon mutations and in those with exon 20 mutations versus other uncommon mutations. We identified 64 relevant studies. Uncommon mutations constituted 1.0–18.2% of all EGFR mutations, across 10 studies. The most frequently reported uncommon mutations were G719X (0.9–4.8% of all EGFR mutations), exon 20 insertions (Ex20ins; 0.8–4.2%), L861X (0.5–3.5%), and S768I (0.5–2.5%). Patients with common mutations typically experienced better treatment response and longer PFS on EGFR-TKIs than patients with uncommon mutations; Ex20ins mutations were associated with less favourable outcomes than other uncommon mutations. This review shows that uncommon mutations may comprise a clinically significant proportion of the EGFR mutations occurring in NSCLC, and highlights disparities in EGFR-TKI sensitivity between different uncommon mutations. Highlights: In stage IIIB/IV NSCLC, 1.0–18.2% of all EGFR mutations are uncommon mutations. G719X, exon 20 insertions, L861X and S768I are the most frequent uncommon mutations. Response to EGFR-TKIs and PFS are better for common rather than uncommon mutations. Outcomes are less favourable with exon 20 insertions versus other uncommon mutations.